Factors that Effect Individual Interest in Using E-Wallet OVO (Case Study on Students in Bandar Pasir Mandoge) - Amhar Maulana Harahap; Junda Harahap (Universitas Muhammadiyah Surabaya, 2023)
A range of innovative financial technologies, including e-wallets, have emerged due to the rapid rise of online transactions. There are 38 e-wallets in Indonesia, including OVO, that have been granted a license by Bank Indonesia. Due to the competition among e-wallets, OVO, the second most well-known e-wallet in Indonesia, has continued to implement a number of improvements to boost OVO usage. OVO e-wallet, on the other hand, is still making an effort to present itself to the public through various promotions. This study intends to ascertain the degree to which perceptions of trust, perceived safety, perceived usefulness, perceived ease of use, perceived risk, and consumptive behaviour, either partially or simultaneously, affect students in Bandar Pasir Mandoge's choice to use the OVO e-wallet. The research method used in this research is associative quantitative research method. The data analysis method used is statistical method with the help of SPSS version 23. The data analysis techniques used in this study are validity test, reliability test, normality test, multicolinerity test, heteroscedasticity test, multiple linear regression test, coefficient of determination, t test, and F test. This study concluded that there is a positive and significant influence either partially or simultaneously between the variables of trust, perceived safety, perceived usefulness, perceived ease of use, perceived risk, and consumptive behaviour of decisions to use the OVO e-wallet.